Dynamic Light Scattering and UV-Vis Spectrophotometric Assessment of Stability of Metal Nanoparticles in Aqueous Medium - Osman Mohamed, Ola Yahia (Universiti Teknologi PETRONAS, 2016)
Stability of gold nanoparticles (AuNPs) has been studied in aqueous and ionic liquid mediums. In each medium four different volumes of oil palm leaf extract has been used as a stabilizer. The effect of the extract volume on the stability of AuNPs in the eight samples has been studied using Dynamic Light Scattering (DLS), UV-Vis spectrophotometry, and Zeta Potential testing methods. The results of the three tests were taken for 5 weeks on a weekly basis and the change of the UV-vis absorbance, surface potential and size results has been used to indicate the stability of the AuNPs in the samples. Moreover the results of particles size as well as the surface potential obtained from the DLS and zeta potential methods were used in calculating the stability ratio based on the DLVO theory. Based on these calculations the change of stability ratio with time was used as a quantitative definition of the nanoparticles stability in the two testing mediums. The obtained results from both the stability ratio and UV-Vis absorbance have shown that addition of the ionic liquid has significantly increased the stability of the gold nanoparticles, however the quantitative results gave more specific.